Environmental and climatic factors associated with the Aedes aegypti occurrence (Research, Society and Development, 2021)
Infestation by the Aedes aegypti mosquito and transmission of associated pathologies such as Dengue fever, Zika virus and Chikungunya fever has been a public health problem in Brazil and in the world. The relationship between environmental and climatic factors and A. aegypti infestation has demonstrated regional specificities, alerting health professionals in the adoption of prevention and control strategies. In view of the above, the present study aimed to evaluate the relationship between environmental and climatic factors with the vector population fluctuation in the municipality of Chapecó, Santa Catarina. Climatic data of monthly minimum, monthly average and monthly maximum temperature, monthly relative humidity, mean monthly atmospheric pressure and monthly total rainfall were obtained from EPAGRI / CIRAM and correlated with the frequency of vector focuses. It was observed that the infestation is not spatially homogeneous and that the type of the property, the type of breeding place, the monthly rainfall, the average temperature and the relative humidity of the air presented significance (p